PB1 S524G mutation of wild bird-origin H3N8 influenza A virus enhances virulence and fitness for transmission in mammals - Xinghai Zhang; Yuanguo Li; Song Jin; Yiming Zhang; Leiyun Sun; Xinyu Hu; Menglin Zhao; Fangxu Li; Tiecheng Wang; Weiyang Sun; Na Feng; Hongmei Wang; et al. (Emerging Microbes and Infections, 2021)
Influenza H3N8 viruses have been recovered frequently from wild bird species, including Anseriformes (primarily from migratory ducks) and Charadriiformes (primarily from shorebirds). However, little attention has been given to the transmission ability of H3N8 avian influenza viruses among mammals. Here, we study the potential human health threat and the molecular basis of mammalian transmissibility of H3N8 avian influenza viruses isolated from wild bird reservoirs. We classified eight H3N8 viruses into seven different genotypes based on genomic diversity. Six of eight H3N8 viruses isolated naturally from wild birds have acquired the ability to bind to the human-type receptor. However, the affinity for α-2,6-linked SAs was lower than that for α-2,3-linked SAs. Experiments on guinea pigs demonstrated that three viruses transmitted efficiently to direct-contact guinea pigs without prior adaptation. Notably, one virus transmitted efficiently via respiratory droplets in guinea pigs but not in ferrets. We further found that the PB1 S524G mutation conferred T222 virus airborne transmissibility between ferrets. We also determined that the 524G mutant increased viral pathogenicity slightly in mice compared with the WT (wild type). Based on these results, we elucidated the potential human health threat and molecular basis of mammalian transmissibility of H3N8 influenza viruses. We emphasized the need for continued surveillance of the H3N8 influenza viruses circulating in birds.